Hubungan Antara Frekuensi Konsumsi Fast Food dan Aktivitas Fisik dengan Tebal Lemak Bawah Kulit Siswi SMA N 6 Yogyakarta - Bayuningsih, Siti Nurrochmah, Toto Suharto, SKM., M.Kes, Elida Soviana, S.Gz., M.Gizi (2015)
Background : Fast food in Indonesia can influence the food habit of the adolescent in town. The female adolescent tend to keep the excessive energy as body fat. The Physical inactivity following by over eating will saving energys in form of fat. In the body, the excessive food intake is converting into fat and strored in adipose tissue. Objective : To analyzed the correlations between fast food consumption frequency and physical activity with skin fold thickness of the female student SMA N 6 Yogyakarta. Methods: This research was observational with cross sectional draft research. The data of the fast food consumption frequency collected by form food frequency in the last one month and the data of physical activity collected by record physical activity for 3 days. The data of skin fold thickness collected by measurement used skinfold caliper. Rank spearman test used to analyzed the correlation between fast food consumption frequency and skin fold thickness. Person correlation test used to analyzed the correlation between physical activity and skin fold thickness. Result: Most of the research subject (54,4%) have often level for fast food consumption frequency. Most of the research subject (68,2%) have light level for physical activity. The research subject have high level for skin fold thickness (skin fold thickness > 30%) as much 36,4% . Conclusion: There was no correlations between fast food consumption frequency and physical activity with skin fold thickness for female student SMA N 6 Yogyakarta.